Influence of corporate and regulatory affairs department on different marketing schemes in Banglalink Digital Communications Ltd. - Ferdous, Sanjida (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.